2021
DOI: 10.6007/ijarbss/v11-i1/8541
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Pay for Kubah National Park: Evidence from the Contingent Valuation Method

Abstract: The purpose of this study is to estimate Kuching residents' (non-visitors) willingness to pay (WTP) for the conservation of Kubah National Park, Sarawak. In order to answer the research objectives in this study, Contingent Valuation Method (CVM) was put into application as the elicitation method and there were 160 respondents who involved in this data collection, where the random sampling method was executed. A dichotomous choice CVM (DC-CVM) was adopted and logit models were used to analyze the CVM analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The marginal effect estimates for the household annual income variable indicated that a one LAK increase in a household's income could increase the probability of WTP for forest maintenance by 28.6%. This finding is consistent with those of many previous studies [42,47,53,[65][66][67].…”
Section: Factor Analysissupporting
confidence: 94%
See 2 more Smart Citations
“…The marginal effect estimates for the household annual income variable indicated that a one LAK increase in a household's income could increase the probability of WTP for forest maintenance by 28.6%. This finding is consistent with those of many previous studies [42,47,53,[65][66][67].…”
Section: Factor Analysissupporting
confidence: 94%
“…In addition, higher educational attainment is viewed favorably by WTP, because it reflects a greater ability to pay. Therefore, the predicted sign of the variable coefficient has a positive influence on WTP [47,[52][53][54][55].…”
Section: Variables Hypothesismentioning
confidence: 96%
See 1 more Smart Citation
“…Currently, the DWNP has little information about visitors’ attitudes and perceptions on elephant conservation (Department of Wildlife and National Parks, 2021; Ghosh et al, 2016). In many cases, policy makers are faced with difficulties in determining a fee that should be imposed in wildlife conservation centers without information on how much visitors are willing to pay for such initiatives (Bakar et al, 2021). This study would offer the relevant authority’s justification for financial allocations while providing a reference on the appropriate amount of entrance fees for the NECC.…”
Section: Introductionmentioning
confidence: 99%
“…This method is useful as it is used in practice to represent the preferences of individuals as well as society in a variety of domains like the environment, education, health care, and others [5] . Valuation studies were conducted in developing countries, covering various types of ecosystems such as wetlands, national parks, and forests [2,9,14]. To manage and protect biodiversity, it is necessary to collect data on the economic worth of biodiversity conservation.…”
mentioning
confidence: 99%